Коран як символ верховної влади (до історії «Самаркандського куфічного Корану») - Резван, Ю. (Народна творчість та етнологія, 2013)
Стаття присвячена історії двох найдавніших рукописів Корану, які протягом століть були символами верховної влади. Обидва рукописи шанувалися як «Корани ‘Усмана» – першосписки Священного тексту. Дванадцятивікова доля названих рукописів – це дивовижна історія, нерозривно пов’язана з долями династій і держав, міст і людей, з долями ісламської цивілізації від її виникнення в Аравії VII ст. до торжества ісламу, що пережив комунізм на теренах мусульманських республік колишнього СРСР. The article deals with the two oldest Quran manuscripts being the supreme power symbols through the centuries. Both manuscripts have been respected as the Uthman Qurans – the primary sources of the Holy Book. The twelve-century fate of these two manuscripts is an out-of-the-way history, which is indissolubly related to the dynasties of the whole dynasties and states, cities and people, to the dynasties of Islamic civilization from its beginning in Arabia in the 7th century to the triumph of Islam, which has gone through Communism in the former USSR Muslim republics' territory.